Method validation for the simultaneous estimation of three-bioactive components in combined extracts of three hepatoprotective plants using RP-HPLC method - Sharuti Mehta&, Anil Kumar Sharma, Rajesh Kumar Singh (Journal of Applied Pharmaceutical Science, 2021)
Picrorhiza kurroa Royle ex Benth. (Scrophulariaceae), Andrographis paniculata (Burm.f.) Nees (Acanthaceae), Silybum marianum (L.) Gaernt (Sm). (Asteraceae) are well-known plants to treat various ailments. Simultaneous quantification and determination of picroside-I, andrographolide, and silybin were conducted in the combined extract of their respective plants, by reverse-phase high performance liquid chromatography (RP-HPLC). Analytical determination of the proposed HPLC method was validated as per International Conference for Harmonization guidelines. Determination and method validation was carried on RP-HPLC column. Picroside-I, andrographolide, and silybin were quantified as 1.232 ± 0.0102, 0.572 ± 0.0734, 2.037 ± 0.0635 µg/mg, respectively. Validated method for simultaneous estimation of analytes was investigated to be linear, specific, reproducible, and accurate. Recovery of identified analytes was within the specified limit of 99.65%–102.59%. The study reveals that the developed HPLC method exhibits potential for determination and quantification of picroside-I, andrographolide, and silybin in in combined extract of P. kurroa, A. paniculata, and S. marianum.
Keywords: Diterpeniod lactone, flavanolignan, high performance liquid chromatography, kalmegh, kutki, milk thistle.